User Satisfaction Evaluation of E-Learning as a Learning System at Heritage School - Gondomulio, Timothy; Suroso, Jarot S. (APIC, 2023)
This study examines the effectiveness of using E-learning in XYZ school. In education, the issue of using information and communication technologies for teaching and learning is of great importance. This study will provide a literature review and scientific background to the study by reviewing the impact of E-learning, particularly its use in teaching and learning in education. At the moment, the school is using an E-learning system called Learning Management System. This study will analyze the user’s satisfaction for the information quality, system quality, service quality, and its use, by using the PLS-SEM application. The results of this study will determine if the user’s are satisfied and if the system needs to be improved.